Hubungan Pemberian MP-ASI dengan Kejadian Stunting pada Anak Usia 6–24 bulan di Posyandu Wilayah Kerja Puskesmas Cigalontang - Rury Kemara Giri; Yuli Susanti; Satryo Waspodo (UNISBA Press, 2022)
Abstract. Indonesia is a country with a high prevalence of stunting. One of the causes of stunting is the lack of complementary feeding to meet nutritional needs at the age of 6–24 months, which cannot be fulfilled if only breast milk is given. The purpose of this study was to determine the relationship between complementary feeding and the incidence of stunting in children aged 6–24 months at the Posyandu in the Work Area of the Cigalontang Health Center. This study used a cross-sectional method. The determination of sample size was based on the hypothesis test formula for two population proportions and obtained a sample size of 80. Univariate data analysis showed the distribution of complementary feeding and the incidence of stunting in children aged 6–24 months, and bivariate analysis was conducted to analyze the relationship between complementary feeding and the incidence of stunting in children aged 6–24 months using the test chi-square. Based on the results of univariate data analysis, it shows that the provision of complementary feeding to children aged 6–24 at the Posyandu in the Cigalontang Health Center working area is mostly inaccurate, and the incidence of stunting shows 30 people in the short category and 5 people in the very short category. Based on the results of data analysis using the method chi-square, a value of 0.197 (p > 0.05) was obtained, so that it can be concluded that there is no relationship between the provision of complementary feeding and the incidence of stunting in children aged 6–24 months at the Posyandu in the Cigalontang Public Health Center. Abstrak. Indonesia merupakan negara dengan prevalensi stunting yang tinggi. Salah satu penyebab stunting adalah pemberian MP-ASI kurang untuk memenuhi kebutuhan gizi pada saat usia 6–24 bulan yang tidak dapat tercukupi apabila hanya diberikan ASI. Tujuan penelitian ini adalah mengetahui hubungan pemberian MP-ASI dengan kejadian stunting pada anak usia 6–24 bulan di Posyandu Wilayah Kerja Puskesmas Cigalontang. Penelitian ini menggunakan metode cross-sectional. Penentuan ukuran sampel berdasar atas rumus uji hipotesis untuk dua populasi proporsi dan didapatkan jumlah sampel 80. Analisis data univariat menunjukkan distribusi pemberian MP-ASI dan kejadian stunting pada anak usia 6–24 bulan serta analisis bivariat dilakukan untuk menganalisis hubungan pemberian MP-ASI dengan kejadian stunting pada anak usia 6–24 bulan menggunakan uji chi-square. Berdasar atas hasil analisis data univariat menunjukkan bahwa pemberian MP-ASI pada anak usia 6–24 di Posyandu Wilayah Kerja Puskesmas Cigalontang sebagian besar kurang tepat dan kejadian stunting menunjukkan 30 orang kategori pendek dan 5 orang sangat pendek. Berdasar atas hasil analisis data dengan menggunakan metode chi-square, diperoleh 0,197 (p > 0,05) sehingga dapat disimpulkan tidak terdapat hubungan pemberian MP-ASI dengan kejadian stunting pada anak usia 6–24 bulan di Posyandu Wilayah Kerja Puskesmas Cigalontang.